Efforts to Improve Motivation and Learning Outcomes with the Use of Powerpoint Media - Siregar, Torang (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2022)
The purpose of this study was to determine the use of powerpoint media to increase motivation and learning outcomes of art and culture with materials for drawing decorative flora and fauna for class VIIIA students of SMP Negeri 02 Padangsidimpuan in the second semester of the academic year 2022/2023. This research was conducted in the second semester of the academic year 2022/2023. The research subjects were 36 students of class VIIIA of SMP Negeri 02 Padangsidimpuan. With the research target is the motivation and learning outcomes of art and culture materials for drawing decorative flora and fauna. Tool to collect data by observation to determine student learning motivation, learning outcomes of art and culture carried out a performance drawing test. This study uses 3 data analyzes, namely initial conditions, cycle 1 data, and cycle 2 data analyzed using comparative description techniques followed by reflection. The method used is to form large groups, small groups using powerpoint media are carried out by drawing performance tests to determine the increase in learning outcomes. This research model uses 4 stages of action: planning, action, observation, and reflection. Based on the results of the study, it was concluded that there had been an increase in the motivation indicator data for cycle 1, indicator 1) 81%, 2) 82%, 3) 87, cycle 2 increased to indicator 1) 83%, 2) 84%, 3) 90%. While the data on learning outcomes in cycle 1, the lowest score was 70, the highest score was 87, the average value was 77, there were 2 students who had not completed, cycle 2 the lowest score was 76, the highest score was 90, the average value was 79, and all the students completed.